Effects of the spermatozoa: oocyte ratio, water volume and water temperature on artificial fertilization and sperm activation of cascudo-preto - Bombardelli, Robie Allan; Sanches, Eduardo Antônio [UNESP]; Baggio, Diego Mendes; Sykora, Renata Marino; Souza, Bruno Estevão de; Tessaro, Lucélia [UNESP]; Piana, Pitágoras Augusto (Sociedade Brasileira de Zootecnia, 2013)
The objective of this study was to evaluate the effects of water volume and water temperature on the sperm motility duration and the number of spermatozoa, and the water volume on the fertilization rates of oocytes of Rhinelepis aspera. Experiments were carried out to evaluate the effect of semen dilutions (1.74×10-5, 1.74×10-4, 1.74×10-3, 1.74×10-2, 1.74×10-1 and 1.00 mL of sperm.mL-1 of water) and water temperature (5, 10, 15, 20, 25, 30, 35, 40, 45, and 50 ºC) on spermatozoa motility duration. In addition, the effects of insemination dose (7×10³, 7×10(4), 7×10(5), 7×10(6) and 7×10(7) spermatozoa.oocyte-1) and water volume (1.0, 30.0, 60.0, 90.0 and 120.0 mL water.2.0 mL-1 oocytes) on the artificial fertilization rates of oocytes were evaluated. The longest sperm motility duration were observed for the semen dilution of 1.74×10-5 mL semen.mL-1 water and in water at 5 ºC. The highest fertilization rates were obtained for insemination doses between 7.00×10³ and 1.23×10(7) spermatozoa. oocyte-1 and water volume of 28.11 mL water.2.0 mL-1 oocytes.
Keywords: fish; Loricariidae; oocyte; reproduction; semen